The book of spells : 150 magickal ways to achieve your heart's desire - Harrison, Ella (DK, 2022)
The complete practical guide to spellcraft, bringing the ancient wisdom of witches into the modern world. Discover the art of spell casting to add some magick to your daily life. Whatever your hopes and dreams, learn how to successfully set your intentions, raise and direct energy, and manifest your desires with 150 simple rituals. From protection and banishment spells to empowering incantations and folk charms for good fortune - each page offers steps to enhance a different aspect of your life, allowing you to take the practice into your own hands and connect to the magick within. This beautifully illustrated guide is overflowing with wisdom to help hone your craft, no matter where you are in your witchcraft journey. Each spell is set out in simple, easy-to-follow steps, ideal for those beginning their witchcraft journey. Beautifully illustrated throughout, this book includes an introduction into witchcraft, the tools you may want to include, and an extensive correspondence of herbs and crystals as well as a simple guide to create your own unique spells and rituals.